Biographical Analysis of Ibn Ishaq's Hadith in the Study of Jarh Wa Ta'dil - Neni Nurjanah; Tajul Arifin; Dadah (al-Afkar, Journal For Islamic Studies, 2025)
This paper discusses the analysis of the biography of Muhammad bin Ishaq bin Yasar (Ibnu Ishaq) in the context of Jarh wa Ta'dil, a branch of hadith studies that evaluates the quality of hadith transmitters. Ibnu Ishaq is known as an influential Islamic historian, but his role as a hadith narrator has often been criticized by scholars. This study covers a brief biography of Ibnu Ishaq, the criticisms (jarh) against him, and the defenses (ta'dil) he received. Criticisms of Ibnu Ishaq include allegations of tadlis (concealing transmitters), weaknesses in the chain of narration (sanad), and negative views from scholars such as Yahya bin Ma'in and Imam Ahmad bin Hanbal. Nonetheless, Ibnu Ishaq's significant contributions to Islamic history are recognized by several prominent scholars. The paper concludes that a deep understanding of the context and methods of Ibnu Ishaq's transmission is necessary to appreciate his contributions without neglecting the fundamental principles of hadith studies.